Strategi Dagang Dan Permasalahan Toko Jepang Di Hindia Belanda Sebelum Perang Dunia II - Stedi Wardoyo (IZUMI, 2019)
(Title: Strategy Of Commerce And Issues Of Japan Shop In The Netherlands Indies Before World War II) The early of 20th century was a turning point of Japanese economic activities in Dutch East Indies, along with increasing number of Japanese population, especially in Java. In that era, Japanese trading activities that dominated by Japanese goods pitchman like textiles, drugs, soap and the other daily necessary untill suburb of Java, changed into permanent economic activities in the form of a small shop that popular among Javanese society in that era as Toko Jepang or Japanese Store.             In the end of 1910 untill early 1940s, Japanese store’s activities were growing and increasing to become an icon in the economic relation between Japan and Dutch East Indies. During that period, there was increase and decrease in Japanese store’s activities, but at the world economic crisis in 1920s, Japanese Market was able to survive, even Japanese products from Japanese Store was better than Chinese and European products. Japanese store, that popular among indigenous was known for it’s good service, cheap price and good quality products.             This research is trying to find how Japanese store can build it’s connection and the factors that supporting and obstacling Japanese store’s growth in that era. In this research, besides the diaries of Japanese immigrants such as Jagatara Kanwa and Nanyou no Seikatsu Kiroku, Japanese newspaper of Touindo Nippou was used as main sources. Content analysis was applied as a method to determine the contents in those sources which were relevant to the topic of this research. It can be concluded that the success keys of Japanese store was marketing strategies that supported by a strong trade connection, beside another factors like the success of observing people’s needs and product marketing strategy.  gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor